Challenges in Design of Positive Isolation System for Large Diameter Gas Piping in Steel Plants - DATTA, ANIRBAN (PREPARE@u® | IEI Conferences, 2021)
In this era of heading to 5 trillion dollar economy, ‘Safety’ remains prime concern for any industrial establishment; steel plant is no exception. During reduction of iron ore, the blast furnace produces blast furnace gas, having considerable calorific value. The gas, however, is not only poisonous, but has potential to form explosive mixture. Apart from blast furnace gas, there are other hazardous gases such coke oven gas, mixed gas etc. which also run through piping system in steel plants. After utilizing optimum heat value of the gas in various shops/units inside the plant, it is often required to release unused/excess gas through flare system. While maintaining the line pressure, the process calls for extreme safety measures against any hazard. ‘Water-seal’ is a conventional requirement at the upstream of branch-out connections or flare stack, which avoids any accidental propagation of fire caused by ingress of air from top of the stack, or from any other source of leakage. In addition, ‘positive isolation’ during maintenance necessitates either U-seal (requiring considerable plant space) or a Goggle Valve (a costlier proposition), in lieu. Designing of the positive isolation for repair/maintenance in large diameter gas piping mains connected to different units/shops/equipment often possess a challenge to the consulting engineer. This paper articulates on those challenges and focuses on a cost-effective, efficient and innovative safety device for flare stack, which can be called ‘Water-Seal-cum-Lock’.